2021
DOI: 10.3389/fimmu.2021.631410
|View full text |Cite
|
Sign up to set email alerts
|

MR1-Restricted MAIT Cells From The Human Lung Mucosal Surface Have Distinct Phenotypic, Functional, and Transcriptomic Features That Are Preserved in HIV Infection

Abstract: Mucosal associated invariant T (MAIT) cells are a class of innate-like T cells that utilize a semi-invariant αβ T cell receptor to recognize small molecule ligands produced by bacteria and fungi. Despite growing evidence that immune cells at mucosal surfaces are often phenotypically and functionally distinct from those in the peripheral circulation, knowledge about the characteristics of MAIT cells at the lung mucosal surface, the site of exposure to respiratory pathogens, is limited. HIV infection has been sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In addition to RORC , we found robust expression of IL17A (Fig. 2c ), concordant with our observations in both peripheral blood 34 and the lung 15 . The highest significantly upregulated gene in lung MAIT cells was SLC4A10.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to RORC , we found robust expression of IL17A (Fig. 2c ), concordant with our observations in both peripheral blood 34 and the lung 15 . The highest significantly upregulated gene in lung MAIT cells was SLC4A10.…”
Section: Resultssupporting
confidence: 91%
“…We found that MAIT cells with mycobacterial reactivity are present in the airways of healthy individuals, and further enriched in bronchoalveolar fluid isolated from patients with active pulmonary tuberculosis 14 . Furthermore, bronchoalveolar MAIT cells from healthy individuals with latent tuberculosis produce less pro-inflammatory cytokines, display higher levels of inhibitory markers, and can express distinct tissue repair genes compared to peripheral MAIT cells 15 . Finally, murine models of bacterial pneumonia have uncovered a key role for MAIT cells in the lungs that proliferate in situ as opposed to being recruited from lymph nodes 16 .…”
Section: Introductionmentioning
confidence: 99%
“…MAIT cells located in lung tissue and lung-associated lymph nodes may not behave the same as those derived from the PBMC (42, 43). We isolated lymphocytes from blood (PBMC), lung tissue, and tracheobronchial lymph nodes collected at necropsy from 4 SIV-infected rhesus macaques (Ellis-Connell et al, manuscript in progress; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Data and plasma from participants who were screened for the Phefumula cohort, a research bronchoscopy study described previously in Muema et al , 2020 (15) and Khuzwayo et al , 2021 (16), were used for this analysis. HIV-positive and HIV-negative adults, between 18-50 years, who were otherwise healthy (no chronic medical conditions, no current or past tobacco use, no current TB symptoms) were recruited from KwaDabeka Community Health Clinic in peri-urban KwaZulu-Natal, South Africa.…”
Section: Methodsmentioning
confidence: 99%